A transitivity analysis of the Mandarin BA construction / Wang Jiaqi - Wang, Jiaqi (2015)
Mandarin BA construction is quite a controversial but frequently-used unique sentence pattern with the most salient characteristic of sentence order. Since it is different from the most frequently-shown sentence order of subject-verb-object (SVO) in Chinese, BA construction tends to follow the pattern of “NP1+BA+NP2+V/VP”. It has been implied that the character of BA plays the role in enabling the post-verbal NP2 to occupy the pre-verbal position. Due to its structural peculiarity, the BA construction has received a considerable attention of grammarians. There have been many voices (L. Wang, 1945; Li and Thompson ,1981; H. Wang, 1984; Tsao, 1987; Li, 1990; Chapell, 1991; Zou, 1995; Cheng, 1998; Wu, 1999; Sybesma,1999; Zhang, 2000; Ding, 2001; Shi, 2002; Xu, 2006) that have mainly attempted to classify the Mandarin BA construction, discuss the nature of the BA construction, explore the meanings and functions of the construction, analyze the syntactic feature of the morpheme BA and its NP, and establish some certain relationship among BA, NPs, and verbs. Although these works have disclosed language facts, they belong either to a descriptive analysis or a transformational framework. However, while the BA-construction is a syntactical structure which appears in daily conversations, systematic analysis of BA-constructions in conversation has been scarce. This dissertation will serve as a step toward understanding the BA-construction in written and spoken discourse from a functional approach, especially from newspaper articles and talk shows. Compared with previous studies (L. Wang, 1945; H. Wang, 1984; Tsao, 1987; Wang, 1995; Liu, 1997; Zhang, 2000; Li, 2001; Shi, 2002; H. Q. Wang, 2003; Xu, 2006), this dissertation will focus on attributes of the BA-construction in newspaper articles and talk shows in Mandarin. It will further develop claims of transitivity made by Hopper and Thompson (1980) and Thompson and Hopper (2000); that is, that BA-constructions are high transitive in Chinese and low transitive in English conversations. However, Hopper and Thompson (1980) only discussed one type of BA-construction, and there have been other studies which oppose their results (Tsunoda, 1981, 1985; Lazard, 1998). Based on these studies, it is worthwhile to investigate the degree of transitivity of Mandarin BA-constructions appearing in newspaper articles and talk shows. Transitivity parameters are the principal tool for the analysis of both written and spoken data in this study. This dissertation is to test the Western speculations of transitivity on the Mandarin BA-construction, which is a step forward towards the application of transitivity across languages. Furthermore, it may be used as a contrastive study with other languages. Key words: Mandarin BA-construction, Transitivity, Conversations